2014
DOI: 10.1021/ac403412n
|View full text |Cite
|
Sign up to set email alerts
|

Transmission FT-IR Chemical Imaging on Glass Substrates: Applications in Infrared Spectral Histopathology

Abstract: Fourier transform-infrared (FT-IR) chemical imaging in transmission mode has traditionally been performed on expensive mid-IR transparent windows such as barium/calcium fluoride, which are more fragile than glass, making preparation in the histopathology laboratories more cumbersome. A solution is presented here by using cheap glass substrates for the FT-IR chemical imaging, which has a high-wavenumber transmission window allowing measurement of the C-H, N-H, and O-H stretches occurring at ca. 2500-3800 cm(-1)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(55 citation statements)
references
References 37 publications
1
54
0
Order By: Relevance
“…All evaluations to this point in this study have been performed on images collected by light transmission, which generally provides the best quality datasets. Other studies have reported using glass slides, 78 which involve a trade-off between practicality and reduction in spectral wavelength bandpass, or reflective glass slides, which require transflection model imaging. Another alternative is to use attenuated total reflection mode sampling, 79 which can offer higher spatial resolution 80 but requires good contact with the sample that can be cumbersome for translation.…”
Section: Resultsmentioning
confidence: 99%
“…All evaluations to this point in this study have been performed on images collected by light transmission, which generally provides the best quality datasets. Other studies have reported using glass slides, 78 which involve a trade-off between practicality and reduction in spectral wavelength bandpass, or reflective glass slides, which require transflection model imaging. Another alternative is to use attenuated total reflection mode sampling, 79 which can offer higher spatial resolution 80 but requires good contact with the sample that can be cumbersome for translation.…”
Section: Resultsmentioning
confidence: 99%
“…4. However, spectra from a non-reflective surface (transparent surface) such as transparent polyvinyl or clear glass (data not shown) are distorted and high absorption effects are observed in the spectral range lower than 1500 cm −1 in comparison with reflective or partially-reflective surfaces [23,[33][34][35]. At wavenumber greater than ∼1500 cm −1 non-reflective surface material are transparent to IR radiation.…”
Section: Spectral Reproducibilitymentioning
confidence: 98%
“…Other interesting alternatives have been proposed such as using glass substrate and limiting the spectral range to the high mid-IR wavenumber window where glass is sufficiently transparent [8]. This may be a viable solution for some particular cases but will probably not be of general applicability as most of the fingerprint region of the spectrum is lost.…”
Section: Substratementioning
confidence: 99%